LETTERS. - Mirsky, Jonathan; Shugaar, Antony; Assayas, Olivier; Dickstein, Morris; Mack, Arien (New York Review of Books, 2013)
Several letters to the editor are presented in response to articles in previous issues including "They Know Much More Than You Think" by James Bamford in the August 15, 2013 issue, "Dante: The Most Vivid Version" by Robert Pogue Harrison in the October 24, 2013 issue, and "After May' What?" by Luc Sante in the July 11, 2013 issue and also includes responses from the authors of the articles.